The haunted castle - Stilton, Geronimo; Cernuschi, Claudio; Grassini, Valentina, 1981- (New York : Scholastic, 2011)
Geronimo Stilton and his family travel to Penny Pincher Castle to visit his uncle, Samuel S. Stingysnout, and tries to uncover who, or what, is behind the creepy occurrences that have been taking place at the castle.
Translation of: Ritorno a rocca taccagna.
"#46"--Spine.
3.9.
3-6.
680L
Keywords: Stilton, Geronimo -- Juvenile fiction; Stilton, Geronimo -- Fiction; Mice -- Juvenile fiction; Castles -- Juvenile fiction; Mice -- Fiction; Castles -- Fiction; Haunted houses -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Action and adventure fiction